Taxus floridana Florida Yew - Edward Gilman (EDIS)
This document provides an overview of Taxus floridana, commonly known as Florida Yew. It describes the plant’s characteristics, including its height, spread, and foliage, which consists of dark green needles. The document also covers the plant’s growth requirements, such as partial shade and well-drained soil, and its moderate drought tolerance. Additionally, it highlights the plant’s uses in landscaping, including as a specimen, hedge, or foundation planting, and offers tips for maintaining its health and appearance. The document emphasizes the importance of conserving this native species, which is found only in a small area of north Florida. Original publication date October 1999.